‘Lnc’-ing Wnt in female reproductive cancers: therapeutic potential of long non-coding RNAs in Wnt signalling - Ong, M.; Cai, W.; Yuan, Y.; Leong, H.; Tan, T.; Mohammad, A.; You, M.; Arfuso, Frank; Goh, B.; Warrier, Sudha; Sethi, G.; Tolwinski, N.; et al. (John Wiley & Sons, 2017)
© 2017 The British Pharmacological Society Recent discoveries in the non-coding genome have challenged the original central dogma of molecular biology, as non-coding RNAs and related processes have been found to be important in regulating gene expression. MicroRNAs and long non-coding RNAs (lncRNAs) are among those that have gained attention recently in human diseases, including cancer, with the involvement of many more non-coding RNAs (ncRNAs) waiting to be discovered. ncRNAs are a group of ribonucleic acids transcribed from regions of the human genome, which do not become translated into proteins, despite having essential roles in cellular physiology. Deregulation of ncRNA expression and function has been observed in cancer pathogenesis. Recently, the roles of a group of ncRNA known as lncRNA have gained attention in cancer, with increasing reports of their oncogenic involvement. Female reproductive cancers remain a leading cause of death in the female population, accounting for almost a third of all female cancer deaths in 2016. The Wnt signalling pathway is one of the most important oncogenic signalling pathways which is hyperactivated in cancers, including female reproductive cancers. The extension of ncRNA research into their mechanistic roles in human cancers has also led to novel reported roles of ncRNAs in the Wnt pathway and Wnt-mediated oncogenesis. This review aims to provide a critical summary of the respective roles and cellular functions of Wnt-associated lncRNAs in female reproductive cancers and explores the potential of circulating cell-free lncRNAs as diagnostic markers and lncRNAs as therapeutic targets. Linked Articles: This article is part of a themed section on WNT Signalling: Mechanisms and Therapeutic Opportunities. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v174.24/issuetoc.